Non-Fungible Token: Suatu Urgensi Serta Konstruksi Hukum Dalam Perspektif Hukum Perjanjian - Cyndiarnis Cahyaning Putri (Widya Yuridika, 2023)
The development of investment law in Indonesia, especially in digital assets, has experienced significant developments. Non-Fungible Token (NFT) is a form of digital asset that is currently widely found in the community. However, from a legal perspective, there is no regulation on NFT and how the legality of NFT transactions is related to the use of cryptocurrencies in it. Having established from the background above, this research aims to analyze the urgency of regulating NFT and how basically the legal construction of the NFT in the contract law perspective. This research is normative research using statute and conceptual approaches. The results of the study finds that the urgency of regulating the legal construction of NFT transactions in Indonesia is to provide legal certainty to investors and is related to the legality of NFT transactions in Indonesia if it is associated with the validity of cryptocurrencies. The legal construction of NFT transactions in Indonesia is that the construction is not a sale and purchase agreement, but instead the legal construction refers to exchange agreement as stated in Article 1541 BW whereas cryptocurrency and NFT here will be given extensive meaning as goods in order to comply with the provisions of Article 1320 of BW to fulfill the objective requirements, in particular, the halal cause.